Dochód gospodarstwa domowego a posiadanie samochodu - Mruk, Henryk (Wydział Prawa i Administracji UAM, 1978)
The analysis of affluence of housekeepings in dependence on possessing a car was carried out on the ground of results of an inquiry of 32 000 respondents. Few selected statistical measures were used to evaluate an affluence level and income distribution of different groups of housekeepings. It results from the analysis, that the housekeepings which possessed cars, had incomes at their disposal, which were about 40 per cent higher than in housekeepings without cars. There was also observed a great differentiation in affluence of housekeepings possessing cars differed in price and type. There is then almost no difference in concentration of incomes which are regularly distributed among affluent groups in motorized housekeepings as well as in unmotorized ones. Distribution of incomes of housekeepings possessing cars is characterized by a lower value of the asymmetry coefficient than in housekeepings without cars.
Income of a Housekeeping and Possession of a Car